Validation of murine and human placental explant cultures for use in sex steroid and phase II conjugation toxicology studies. Issue 1 (February 2015) - Sato, Brittany L.; Ward, Monika A.; Astern, Joshua M.; Kendal-Wright, Claire E.; Collier, Abby C.
Highlights Human placental explants are validated for cytokine but not sex steroid studies. Mouse placental explant cultures have not previously been examined. We assessed ex vivo culture of both species for steroidogenic and clearance traits. Human explants may be used for metabolism and clearance, but not endocrine studies. Mouse explants may be used for steroidogenesis, but not phase II metabolism studies.